Ocean acidification during prefertilization chemical communication affects sperm success - Rowan A. Lymbery; W. Jason Kennington; Christopher E. Cornwall; Jonathan P. Evans (Ecology and Evolution, 2019)
Abstract Ocean acidification (OA) poses a major threat to marine organisms, particularly during reproduction when externally shed gametes are vulnerable to changes in seawater pH. Accordingly, several studies on OA have focused on how changes in seawater pH influence sperm behavior and/or rates of in vitro fertilization. By contrast, few studies have examined how pH influences prefertilization gamete interactions, which are crucial during natural spawning events in most externally fertilizing taxa. One mechanism of gamete interaction that forms an important component of fertilization in most taxa is communication between sperm and egg‐derived chemicals. These chemical signals, along with the physiological responses in sperm they elicit, are likely to be highly sensitive to changes in seawater chemistry. In this study, we experimentally tested this possibility using the blue mussel, Mytilus galloprovincialis, a species in which females have been shown to use egg‐derived chemicals to promote the success of sperm from genetically compatible males. We conducted trials in which sperm were allowed to swim in gradients of egg‐derived chemicals under different seawater CO2 (and therefore pH) treatments. We found that sperm had elevated fertilization rates after swimming in the presence of egg‐derived chemicals in low pH (pH 7.6) compared with ambient (pH 8.0) seawater. This observed effect could have important implications for the reproductive fitness of external fertilizers, where gamete compatibility plays a critical role in modulating reproduction in many species. For example, elevated sperm fertilization rates might disrupt the eggs' capacity to avoid fertilizations by genetically incompatible sperm. Our findings highlight the need to understand how OA affects the multiple stages of sperm‐egg interactions and to develop approaches that disentangle the implications of OA for female, male, and population fitness.